174k views
4 votes
Two 2.3 kg bodies, A and B, collide. The velocities before the collision are and . After the collision, . What are (a) the x-component and (b) the y-component of the final velocity of B? (c) What is the change in the total kinetic energy (including sign)?

1 Answer

6 votes

Missing details in the question:

The velocities before collision are


u_A=(40i+49j) m/s


u_B=(35i+11j) m/s

After the collision:


v_A=(14i+21j) m/s

(a) 61 m/s

We can solve the problem by simply treating separately the x- and the y-components of the motion.

Here we want to analzye the motion along x. We have:


u_A = 40 m/s is the initial velocity of A along the x-direction


u_B = 35 m/s is the initial velocity of B along the x-direction


v_A = 14 m/s is the final velocity of A along the x-direction


v_B = ? is the final velocity of B along the x-direction

Since the total momentum along the x-direction must be conserved, we can write


mu_A + mu_B = mv_A + mv_B

where

m = 2.3 kg is the mass of the two bodies. Since the mass is the same, we can eliminate it from the equation,


u_A + u_B = v_A + v_B

And so, we find the final velocity of B along the x-direction:


v_B = u_A + u_B - v_A=40+35-14=61 m/s

(b) 39 m/s

Similarly to what we did in part a), here we analyze the conservation of momentum along the y-direction.

We have:


u_A = 49 m/s is the initial velocity of A along the y-direction


u_B = 11 m/s is the initial velocity of B along the y-direction


v_A = 21 m/s is the final velocity of A along the y-direction


v_B = ? is the final velocity of B along the y-direction

Since the total momentum along the y-direction must be conserved, we can write


mu_A + mu_B = mv_A + mv_B

Since the mass is the same, we can eliminate it from the equation,


u_A + u_B = v_A + v_B

And so, we find the final velocity of B along the y-direction:


v_B = u_A + u_B - v_A=49+11-21=39 m/s

c) +615 J

Here we have to find the total kinetic energy before and after the collision first.

First, we have to find the speed of each object before and after the collision. We have:


u_A = √(40^2+49^2)=63.2 m/s\\u_B = √(35^2+11^2)=36.7 m/s\\v_A = √(14^2+21^2)=25.2 m/s\\v_B = √(61^2+39^2)=72.4 m/s

So, the total kinetic energy before the collision was


K_i = (1)/(2)mu_A^2+(1)/(2)mu_B^2 = (1)/(2)(2.3)(63.2)^2+(1)/(2)(2.3)(36.7)^2=6143 J

While after the collision


K_f = (1)/(2)mv_A^2+(1)/(2)mv_B^2 = (1)/(2)(2.3)(25.2)^2+(1)/(2)(2.3)(72.4)^2=6758 J

So, the change in kinetic energy is


\Delta K = K_f - K_i = 6758-6143 = +615 J

(note that the system cannot gain kinetic energy in the collision, unless there is an external force acting on it)

User Ililit
by
5.6k points